Diversified agriculture leads to diversified diets: Panel data evidence from Bangladesh - Mastura, Tamanna; Begum, Ismat Ara; Kishore, Avinash; Jackson, Tamara; Woodhill, Jim; Chatterjee, Kuhu; Alam, Mohammad Jahangir (Frontiers Media, 2023)
This study used a panel data model to examine the relationship between agricultural diversification and dietary diversity of farm households across three waves of nationally representative Bangladesh Integrated Household Survey data (BIHS- 2011-12, 2015, and 2018). Prior research measured diversification in terms of crop cultivation and livestock rearing. However, this study takes a different approach to measuring agricultural diversification by combining the three major sectors—crop, fish, and livestock production—at the farm household level to evaluate the impact of such agricultural diversification on the diversification of diets in households. The panel data allows us to establish that agricultural production diversification has a significantly positive effect on the dietary diversity of farm households. Moreover, other important factors that impact agricultural diversification to improve dietary diversity, like women’s employment, market access, engagement with non-farm income sources, and access to information also have a strong association in improving the dietary status, food and nutritional security of households. Participation in the market helps farming households to become more commercially oriented but negatively affects the dietary diversification of the households. However, participation in non-farming activities was reported to have a significant positive influence on dietary diversity, though not as much as agricultural diversification. From the perspective of policy that requires nutrition into consideration, the findings suggest to focus on providing support for diversified farming systems can directly increase the nutritionally enriched dietary intake, increasing the employability of women. Promoting market participation through modern infrastructural facilities should be prioritized to improve the current scenarios.